Facilitating EFL Students’ Learning Listening Subject through English Songs: The Audio-Lingual Method Perspectives - Abdul Karim, Sayit; Sudiro, Suryo; Aisyah Putri, Shifani; Syailendra, Axel; Lestari, Putri (English Education Department, 2023)
Listening skill is considered to be a challenging activity for English as a Foreign Language (EFL) learners in the context of English language learning. The present article aims at discussing the utilization of English songs as one of the learning sources for learning listening skills for EFL learners from the perspective of the Audio-Lingual Method (ALM). A qualitative descriptive research design was applied to scrutinize how English songs benefit for EFL learners to facilitate their listening subject. The data were obtained from previous related research findings and documentation studies. Furthermore, it discusses the relationship between song and listening, song as media to facilitate listening skills, the reasons for why using the songs as the learning media, the implication of using the songs to improve listening skills, and the benefits of using English song as a learning media. Review literature shows that the utilization of English songs may improve students’ listening skills and pronunciation over time. The ALM may assist learners in systematically learning the language by playing audio files. Students can comprehend brief and easy sentences when music is played in the background. English songs may assist learners in improving their listening skills and can be used for a variety of learning objectives. From the perspective of the ALM, English songs allow students to better understand the language being taught because it needs a high level of concentration as purposed by the ALM teaching and learning characteristics. In conclusion, from the perspective of ALM, English songs may bring positive contribution to the development of EFL students’ listening skills for some reasons.